Модель оптимізації виробничої потужності підприємства - Степанова, О. В.; Степанов, С. В. (ХНУРЕ, 2017)
At article to optimize production capacity of enterprise it was proposed to solve as task of maximum network flow, and to find problem places at mixed production flow – to use the binary maximum flow task
Keywords: модель оптимізації; потужність підприєчства